Engaging People Prior to Problems: Providing Drinking Water for Villages in South Kalimantan, Indonesia - Shane Elson (Sekolah Pascasarjana Universitas Brawijaya, 2019)
In 2012, a report by the Kabupatan Banjar (South Kalimantan) identified 35 villages of approximately 40,000 residents, in grave need of drinking water. I initially engaged a local non-profit, Yayasan Kaganangan Banua and in time, a local engineering consultancy, Solusi Berinovasi Indonesia. With a team of Indonesians and some expatriates, we began creating a local, sustainable, reproducible, and culturally acceptable solution. By applying action research, we have the flexibility to develop more effective solutions through a series of ongoing iterations in real time. First we listened to the people, understanding them and building trust. This enabled us to establish buy-in which formed the foundation to begin challenging cultural norms in the areas of health and water use. Only then could we begin constructing the infrastructure. The systems are made entirely from local materials and we train locals in both the health education and construction techniques for the purpose of sustainable replication. Today, this project has successfully provided drinking water, year round, to over 500 people with a annual economic impact of over 500 juta across 70 systems in 6 villages. In addition, our team is contributing to most of the SDGs. When we focus first on people and genuine community relationships, regardless of nationality, age, religion, language or culture, we can together overcome the hardest problems and see generational transformation.